12-hydroxy oleic acid impairs endothelium-dependent vasorelaxation. Issue 5 (4th March 2019) - Bass, Virginia L.; Snow, Samantha; Soukup, Joleen; Schladweiler, Mette; Ghio, Andrew; Kodavanti, Urmila; Madden, Michael C.
ABSTRACT: Diesel and biodiesel emissions exposures reduce vascular responsiveness in vivo, but the components of PM responsible for this effect are poorly understood. Fatty acids (FAs) represent a significant fraction of the compounds that make up organic combustion by-products, and may be involved in vascular responses following inhalation. It was hypothesized that vascular tissue exposed to a model FA might impair responses to vasoactive agonists ex vivo . Rat aortic rings were exposed to oleic acid or 12-hydroxy oleic acid and responses determined by myography. 12-Hydroxy oleic acid was found to significantly reduce endothelium-dependent vasodilation at sub-cytotoxic concentrations. This approach demonstrates the potential for FAs, especially oxidized forms, to play a role in the vascular responses observed following air pollution exposure.